Deciphering the Evolution of Cephalosporin Resistance to Ceftolozane-Tazobactam in Pseudomonas aeruginosa - Barnes, Melissa D. (mBio, 2018)
Pseudomonas aeruginosa produces a class C β-lactamase (e.g., PDC-3) that robustly hydrolyzes early generation cephalosporins often at the diffusion limit; therefore, bacteria possessing these β-lactamases are resistant to many β-lactam antibiotics. In response to this significant clinical threat, ceftolozane, a 3′ aminopyrazolium cephalosporin, was developed. Combined with tazobactam, ceftolozane promised to be effective against multidrug-resistant P. aeruginosa. Alarmingly, Ω-loop variants of the PDC β-lactamase (V213A, G216R, E221K, E221G, and Y223H) were identified in ceftolozane/tazobactam-resistant P. aeruginosa clinical isolates. Herein, we demonstrate that the Escherichia coli strain expressing the E221K variant of PDC-3 had the highest minimum inhibitory concentrations (MICs) against a panel of β-lactam antibiotics, including ceftolozane and ceftazidime, a cephalosporin that differs in structure largely in the R2 side chain. The k(cat) values of the E221K variant for both substrates were equivalent, whereas the K(m) for ceftolozane (341 ± 64 µM) was higher than that for ceftazidime (174 ± 20 µM). Timed mass spectrometry, thermal stability, and equilibrium unfolding studies revealed key mechanistic insights. Enhanced sampling molecular dynamics simulations identified conformational changes in the E221K variant Ω-loop, where a hidden pocket adjacent to the catalytic site opens and stabilizes ceftolozane for efficient hydrolysis. Encouragingly, the diazabicyclooctane β-lactamase inhibitor avibactam restored susceptibility to ceftolozane and ceftazidime in cells producing the E221K variant. In addition, a boronic acid transition state inhibitor, LP-06, lowered the ceftolozane and ceftazidime MICs by 8-fold for the E221K-expressing strain. Understanding these structural changes in evolutionarily selected variants is critical toward designing effective β-lactam/β-lactamase inhibitor therapies for P. aeruginosa infections.